The Effect of Entrepreneurship Education on Entrepreneurial Intention in Indonesia - Patricia Patricia; Christian Silangen (Universitas Pelita Harapan, 2016)
This research studied the relationship between entrepreneurship education and entrepreneurial intention of university students. Following original research by Zhang, Duysters, Cloodt (2014), Ajzen's theory of planned behavior and Shapero's entrepreneurial event model would be incorporated to identify the effect of exogenous variables such as entrepreneurship education, prior entrepreneurial exposure, perceived desirability and feasibility towards entrepreneurial intention in university students. Furthermore, this study aimed to investigate the selection hypothesis of entrepreneurship education for entrepreneurial intentions. Lastly, this study was also proposing to investigate the moderating effect of the teachers and instructors' enthusiasm (Frenzel et al., 2009), pre-educational entrepreneurship intention (Bae et al., 2014), gender (Verheul et al., 2012), as well as the moderating effect of peers in the classroom (Falck et al., 2012). The data would be collected from one of the private and reputable universities in Indonesia in multiple departments with a form of entrepreneurship education. In this study we found that entrepreneurship education does shape entrepreneurial intention. Students with pre-educational entrepreneurial intention would be more likely to have higher entrepreneurial intention. We also learned that there’s a strong relationship between social influence of classmates and entrepreneurial intention. In addition, we found that male and female students have a different perspective about entrepreneurship education that affected their entrepreneurial intention.